Linguagem, imaginação e imagem: manifestações do numinoso em Dora Ferreira da Silva - Campos, Fernanda Cristina de (2018)
This thesis covers the lyrical work of Dora Ferreira da Silva and aims at examining the poetic images in their dreamlike and sacred nature, an origin that refers to the romantics and to the Depth Psychology. Her poetic construct ranges from an imagery that privileges the mythical-poetic celebration based on archetypes that evoke the four cosmic elements, fire, water, air and earth, transforming them into a powerful linguistic construct. Hence, important courses were followed in order to obtain a meaningful study of this lyricism: the sacred one, the linguistic one, the one of the material imagination as well as the one of the images. . For such investigations, Gaston Bachelard's phenomenological itinerary was traversed, which, through the theory of material imagination, retrieved the value of imagination from the systematic ordering of the first scholars of this subject, the German romanticists, especially Novalis. The Jungian conception of the archetypal images was imperative for the appreciation to open to the plurisignification of the image-words. While this research was carried out, we also invoked the studies of Rudolph Otto, Martin Heidegger, Friedrich Nietzsche, Gilbert Durand, Benedito Nunes, Hugo Friedrich and Michael Hamburger; researchers who recognize the lyrical trajectory founded on experiences that interconnect daydreams, thoughts and image. In the end, in the poetry of Dora Ferreira da Silva, pure lyricism was recognized while entering numinous domains. This conserves and multiplies the vital force of poetry in the context of contemporary literature.